ADOPTION BY SAME-SEX COUPLES - Kukhianidze, Ketevan (European Scientific Journal, ESJ, 2013)
Kindness, love and compassion are vital values of humanity. They are also the basic principles for a family home for any child. It is commonly believed that children are the important part of the family. But unfortunately, nowadays, there are groups of children who do not have parents or relatives and are hoping for permanent homes. In this case adoption is considered as the necessary, legal process by which a child is placed into a loving, stable home. The need for adoptive families is tremendous, but the process of adopting a child can prove to be quite difficult, especially, when the potential adopters are same-sex couples, who are willing to adopt children and create a family together. Currently, not all states permit same-sex couples to adopt. Many lesbian, gay, and bisexual people would like to be parents. In this situation second parent adoption (also called a co-parent adoption), joint adoption and equitable adoption are the ways for such couples to become legal parents of children.